2015
DOI: 10.1186/s40561-015-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for smarter learning: tales from the trenches

Abstract: Gamification has been explored recently as a way to promote content delivery in education, yielding promising results. However, little is known regarding how it helps different students experience learning and acquire knowledge. In this paper we study and analyze data from a gamified engineering course, to search for distinct behavior patterns. We examined data collected from two gamified years, between which game changes took place. By clustering students according to their performance, we identified three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
2
35
0
11
Order By: Relevance
“…In addition, the participants reported that the blended learning environment supported with gamification increased motivation as it was influential on experience point, going up in levels, competition, winning awards and being in higher positions in leaderboard. This finding is consistent with the findings of other studies in related literature which reported that gamification have positive influence on motivation (Barata, Gama, Jorge, & Goncalves, 2015;Bell, 2014;Buckley & Doyle, 2014;Dicheva et al, 2015;Kuo & Chuang, 2016;Hamari, 2013;Hamari & Koivisto, 2015;O'Donovan, Gain & Marais, 2013;Sailer, et al, 2017;Tauer & Harackiewicz, 2004). In addition, as mentioned by Zichermann and Cunningham (2011), going up in levels contributed to the participants' feeling of achievement.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the participants reported that the blended learning environment supported with gamification increased motivation as it was influential on experience point, going up in levels, competition, winning awards and being in higher positions in leaderboard. This finding is consistent with the findings of other studies in related literature which reported that gamification have positive influence on motivation (Barata, Gama, Jorge, & Goncalves, 2015;Bell, 2014;Buckley & Doyle, 2014;Dicheva et al, 2015;Kuo & Chuang, 2016;Hamari, 2013;Hamari & Koivisto, 2015;O'Donovan, Gain & Marais, 2013;Sailer, et al, 2017;Tauer & Harackiewicz, 2004). In addition, as mentioned by Zichermann and Cunningham (2011), going up in levels contributed to the participants' feeling of achievement.…”
Section: Discussionsupporting
confidence: 91%
“…Sawyer and Smith (2009) as well as Jantke (2012:86) believe that almost every game is a serious game, as there is a serious element in every game. Barata et al (2015) make the following distinction between gamification and serious games:…”
mentioning
confidence: 99%
“…Apesar disso,é interessante reforçar que a coleta de dados qualitativos pode ter um valor muito grande principalmente no entendimento de como os mecanismos de gamificação são percebidos pelos usuários do processo [Iosup and Epema 2014], o queé um feedback valioso para entender como a abordagem afeta o aprendizado e como ela pode ser modificada para engajar um perfil específico de usuário [Barata et al 2015].…”
Section: Tipo De Estudo Total De Artigosunclassified
“…Vale a pena destacar que alguns trabalhos iniciaram a exploração de outros elementos de jogos, como o feedback rápido ( [Holman et al 2013]), sistema de níveis de usuário e progressão no curso ([Berkling and Thomas 2013]), avatares ( [Krause et al 2015]) e missões ( [Barata et al 2015]), e constituem primeiros passos na busca por elementos de jogos que possam tratar a motivação estudantil em um aspecto de médio e longo prazo de forma mais efetiva.…”
Section: Elementos De Jogos Utilizadosunclassified